'A Scorneful Image of this Present World': Translating and Mistranslating Erasmus's Words in Henrician England. Issue 3 (1st September 2022) - Baratta, Luca
Abstract: Many of Erasmus of Rotterdam's works were translated into English during the reign of Henry VIII. In the process of translation, the original intention of these texts was often subverted, as Erasmus's reputation was appropriated by his translators and their patrons to serve a variety of political and religious agendas. The present article is devoted to the translating history of one of Erasmus's works, Sileni Alcibiadis, a proverb that was detached from the huge paremiographic repository known as Adagia and published as an autonomous work in London in the early 1540s. By highlighting corrections, retouchings and omissions, the article aims at pointing out the ways in which the anonymous translator adapted Erasmus's text to a different cultural and pedagogic context. The final purpose of this work is to show the way in which Erasmus's political thought 'migrates', with partial manipulations, into the turbulent context of mid-sixteenth-century England.